The Effectiveness of the Project Based Learning Model on Writing Skills in Senior High Schools - Citra Agustina; Sumarno (Journal for Lesson and Learning Studies, 2026)
Writing skills are an important indicator of literacy competence in senior high school. However, writing instruction is still largely conventional, limiting students’ ability to express ideas systematically, creatively, and critically. This study aims to examine the effectiveness of project-based learning in improving students’ writing skills in senior high school.This study employed a Systematic Literature Review (SLR) approach, involving an in-depth analysis of scientific articles published between 2021 and 2025. This SLR was conducted to gather the latest empirical evidence, minimize bias, and synthesize findings from various sources. The literature search was conducted through Google Scholar using keywords such as "project-based learning models," "writing skills," and "in senior high schools." The searched articles were then selected based on criteria, resulting in a number of relevant articles for analysis. The study results indicate that project-based learning models have a positive impact on improving students' writing skills, particularly in the areas of idea development, text structure, creativity, and higher-order thinking skills. Furthermore, project-based learning plays a role in building a more active, collaborative, and contextual learning process, enabling students to engage more optimally. These findings indicate that the PjBL model is a suitable alternative learning strategy for teaching writing in high schools. The implications of this research emphasize the importance of curriculum support and improving teacher competency in implementing PjBL sustainably to support the improvement of the quality of the learning process in line with educational demands.